In search of lost truth: social media and disinformation - López-Borrull, Alexandre (Anuario ThinkEPI, 2023)
Social media and platforms present a real challenge in the fight against disinformation; however, it is not only a matter of content curation—it is also necessary to reflect on the role that the truth must have on society as a whole. This article makes connections between the business models of platforms, the use of users in wartime moments, and how post-truth and immediacy bring about a certain “social truth”